Charge-tuning of glycosaminoglycan-based hydrogels to program cytokine sequestration. (24th July 2019) - Freudenberg, Uwe; Atallah, Passant; Limasale, Yanuar Dwi Putra; Werner, Carsten
Abstract : Glycosaminoglycan (GAG)-based biohybrid hydrogels of varied GAG content and GAG sulfation pattern were prepared and applied to sequester cytokines. Abstract : Glycosaminoglycan (GAG)-based biohybrid hydrogels of varied GAG content and GAG sulfation pattern were prepared and applied to sequester cytokines. The binding of strongly acidic and basic cytokines correlated with the integral space charge density of the hydrogel, while the binding of weakly charged cytokines was governed by the GAG sulfation pattern.